2011
DOI: 10.1136/sextrans-2011-050108.294
|View full text |Cite
|
Sign up to set email alerts
|

P2-S1.16 Social influences on relationship fidelity and concurrency patterns among Latino adolescents in San Francisco

Abstract: BackgroundOur previous research in San Francisco's Mission District, a predominantly Latino neighbourhood characterised by high immigration, poverty, and gang-related violence, highlighted diverse partnership patterns among youth and the role of gang affiliation in high-risk sexual activity and pregnancy. 38% of Latino youth reported concurrent partnerships.MethodsWe conducted 33 semi-structured in-depth interviews with immigrant and US-born male and female Latino youth aged 16–21 to explore how the social env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Male gang involvement has been associated with perpetration of partner violence (15), inconsistent condom use, increased number of partners, and sexual concurrency (1618). Our past research also found that having a male partner in a gang increased pregnancy incidence among teen females (16) and that gang norms promoted partner concurrency and substance use as signs of masculinity (12). …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Male gang involvement has been associated with perpetration of partner violence (15), inconsistent condom use, increased number of partners, and sexual concurrency (1618). Our past research also found that having a male partner in a gang increased pregnancy incidence among teen females (16) and that gang norms promoted partner concurrency and substance use as signs of masculinity (12). …”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, gang membership may be aligned with culturally-based masculinity norms that can lead to hyper-masculinity among young males (11), thereby increasing sexual risk-taking. In underserved neighborhoods with widespread community violence, the presence of street gangs constitutes a dominant influence on adolescents’ social norms and individual behaviors (1214). Male gang involvement has been associated with perpetration of partner violence (15), inconsistent condom use, increased number of partners, and sexual concurrency (1618).…”
Section: Introductionmentioning
confidence: 99%
“…Having a trusted partner is important in adolescent Hispanic relationships (Laborde et al, 2014). On the other hand, infidelity was common in relationships with Hispanic youth (Minnis and Van Dommelen-Gonzalez, 2011). Hispanic women appear to expect and tolerate some infidelity in their dating relationships, but fidelity became more important once married (Mclellan-Lemal et al, 2013).…”
Section: Relationship Characteristicsmentioning
confidence: 99%
“…In many economically disadvantaged neighborhoods, street gangs constitute a prominent feature of the social environment and assume tremendous influence over social norms and individual behaviors (Voisin et al 2011; Minnis and vanDommelen-Gonzalez 2011; Marcus 2009). Gang affiliation offers social identity, friendship, protection, and an economically viable direction for some youth with limited socioeconomic opportunities (Kyriacou et al 1999; Bennett et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gang-related neighborhood violence has been associated with perpetration of partner violence (Reed et al 2009) and engagement in risky sex behaviors such as inconsistent condom use, increased number of partners, and partnerships that overlap in time (Voisin et al 2004; Crosby et al 2004; Wingood et al 2002). We have found that having a male partner in a gang increased pregnancy incidence among female adolescents by 90% (Minnis et al 2008) and that gang norms promoted partner concurrency and substance use as signs of masculinity (Minnis and vanDommelen-Gonzalez 2011). …”
Section: Introductionmentioning
confidence: 99%